2016
DOI: 10.4049/jimmunol.1501717
|View full text |Cite
|
Sign up to set email alerts
|

MASP-1 and MASP-2 Do Not Activate Pro–Factor D in Resting Human Blood, whereas MASP-3 Is a Potential Activator: Kinetic Analysis Involving Specific MASP-1 and MASP-2 Inhibitors

Abstract: It had been thought that complement factor D (FD) is activated at the site of synthesis, and only FD lacking a propeptide is present in blood. The serum of mannose-binding lectin–associated serine protease (MASP)-1/3(−/−) mice contains pro-FD and has markedly reduced alternative pathway activity. It was suggested that MASP-1 and MASP-3 directly activate pro-FD; however, other experiments contradicted this view. We decided to clarify the involvement of MASPs in pro-FD activation in normal, as opposed to deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 39 publications
2
95
0
Order By: Relevance
“…Numerous studies have shown that MASP-1 activates MASP-2 as an essential step in the activation of the LP (5759). Additionally, other studies have shown that MASP-1 can activate MASP-3 (60, 61). Together, these data suggest that MASP-3 is the primary activator of the AP via cleavage of pro-Df while MASP-1 is the primary activator of the LP via activation of MASP-2.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies have shown that MASP-1 activates MASP-2 as an essential step in the activation of the LP (5759). Additionally, other studies have shown that MASP-1 can activate MASP-3 (60, 61). Together, these data suggest that MASP-3 is the primary activator of the AP via cleavage of pro-Df while MASP-1 is the primary activator of the LP via activation of MASP-2.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore the AP activation seen in mice MASP-1/3 −/− /fH −/− could be due to the formation of CVF-fB convertase in the presence of proDf and if so then these observations will be consistent regarding the activation of AP in fD −/− mice (39). Orozslan and colleagues recently published data in support of MASP-3 being the primary family member involved in the cleavage of proDf (40). This study has also provided evidence as to why only MASP-3 cleaves proDf as it is resistant to C1inhibitor and antithrombin, in contrast to MASP-1 or MASP-2.…”
Section: Discussionmentioning
confidence: 99%
“…However, MASP-3 can be produced by other tissues (40). Nonetheless the cleavage of proDf into Df by MASP-1/3 takes place in the extracellular space and circulation, as it is evident from our studies related to transplantation of liver under the kidney capsule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first we determined the cleavage rates of pro‐FD by all three MASPs testing both the activated and proenzyme forms, and by thrombin. All active MASPs and thrombin were found to be efficient pro‐FD activators in vitro, on the other hand the proenzymes had no significant activity . These results imply that pro‐FD can probably be activated by various active proteases with P1 Arg specificity in vitro, and the real question is which one of these enzymes (or another enzyme) is in the active form when pro‐FD activation takes place.…”
Section: Interactions With Other Complement Pathwaysmentioning
confidence: 94%